Evidence Against Female Victims of Adult Sexual Violence - Labibah, Hanin Alya'; Lestari, Arum Ayu (Jurnal Hukum Magnum Opus, 2025)
In the Criminal Procedure Law, in proving a case, one of the conditions must have a minimum of 2 (two) witnesses, this becomes a problem when this condition is combined with the crime of sexual violence, based on most of the facts that occur in the field, sexual violence experienced by the victim is not necessarily known by others. The purpose of this study is to find out and analyze the crime of witness sexual violence as one of the important aspects of procedural law, as well as to find out the position of electronic evidence in the crime of sexual violence. This type of research is normative legal research with a conceptual approach and a legislative approach. From this study, it can be concluded that in the case of a problem where the crime is difficult to find witnesses, because it happened in a closed place, then 2 witnesses cannot be used as the main evidence for the defendant to be declared guilty because basically, the various pieces of evidence mentioned in Article 184 of the Criminal Code have equal status so that the judge can choose which 2 pieces of valid evidence can give confidence to the judge to determine a person guilty or not. Furthermore, electronic evidence can be used as valid evidence in the crime of adult sexual violence as stipulated in Article 5 paragraph (1) of the ITE Law, the position of electronic evidence as an extension of valid evidence in the Criminal Code.